Immediate Effects of Education on the Manual Ankle Anterior Drawer Test: A Study Using Cadaveric Ankles and Three-Dimensional Kinematic Analysis - Hirofumi Nakajima MD; Satoshi Yamaguchi MD, PhD; Seiji Kimura MD, PhD; Manato Horii MD, PhD; Kaoru Toguchi MD; Ryu Ito MD; Takahisa Sasho MD, PhD; Seiji Ohtori MD, PhD (Foot & Ankle Orthopaedics)
Category: Ankle; Trauma Introduction/Purpose: Manual anterior drawer test (ADT) is widely used for evaluating ankle instability. However, implementing the maneuver with an appropriate method and correct assessments is challenging, particularly for less experienced examiners. An effective strategy to learn the proper technique is mandatory. However, no study has investigated the effect of education on the ADT. This study aimed to clarify whether an educational workshop for senior orthopaedic residents will improve ankle kinematics during the ADT and instability assessment. Methods: The subjects were 20 senior orthopaedic residents. Three fresh-frozen cadaveric ankles were used to create intact, anterior talofibular ligament (ATFL)-cut, and ATFL/calcaneofibular ligament (CFL)-cut models. Infrared markers were attached to the tibia and talus, and three-dimensional kinematics of the ankle joint were measured using a motion capture system (Figure), with the primary outcome being the ATFL length change during the ADT. Examiners first performed the maneuver on the three ankles using their own methods. The examiners also assessed ankle instability in three grades compared to the contralateral side. Subsequently, a one-hour educational workshop consisting of documents, videos, and hands-on sessions was conducted. Afterward, the examiners performed the ADT again on the same three ankles. The ATFL length changes were compared before and after the workshop using paired t-tests. The ankle instability assessments were compared using Chi-square tests. Results: Before the educational workshop, the ATFL length changes were 2.4 ± 0.8 mm, 7.6 ± 3.0 mm, and 6.1 ± 2.7 mm in the intact, ATFL-cut, and ATFL/CFL-cut ankles, respectively. The ATFL length changes significantly increased to 3.2 ± 1.2 mm (P = 0.02), 10.0 ± 2.5 mm (P = 0.005), and 8.4 ± 2.4 mm (P = 0.007) after the workshop. Before the educational workshop, 9 (45%), 7 (35%), and 7 (35%) examiners assessed ankle instability correctly for the intact, ATFL-cut, and ATFL/CFL-cut ankles, respectively. The number of examiners with correct assessments did not increase in either ankles after the workshop (P = 0.14–0.81). Conclusion: We found that the ADT technique, evaluated using cadaveric ankle models and three-dimensional kinematic analysis, improved after the educational workshop for senior orthopedic residents. However, the ankle instability assessments did not change. The short-period workshop, including the lecture and hands-on sessions, successfully improved the ADT maneuver. However, further research is required to determine a more effective training method for correct assessments.